A Blockchain-based and AI-Endorsed Mechanism to Support Social Networks on Fake News Containment - Graciano Neto, Valdemar Vicente; Barbosa, Jacson Rodrigues; Lima, Eliomar Araújo de; Carvalho, Sérgio Teixeira de; Venzi, Samuel (Anais do Brazilian Workshop on Social Network Analysis and Mining (BraSNAM), 2024)
Online Social Networks (OSNs) have promoted, yet unintentionally, critical consequences of fake news dissemination. However, the mainstream OSNs are centralized, while Secure Social Networks (SSNs) are not as popular as the centralized ones. To bridge this gap, this paper proposes a solution using blockchain and artificial intelligence to enhance OSN security by introducing a mechanism for content verification, fact-checking, and rewarded participation. Preliminary proof-of-concept results demonstrate the feasibility of the approach to face misinformation.